2021
DOI: 10.3390/cancers14010063
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vulvar Cancer on Psychosocial and Sexual Functioning: A Literature Review

Abstract: Women who are diagnosed and treated for vulvar cancer are at higher risk of psychological distress, sexual dysfunction and dissatisfaction with partner relationships. The aim of this article is to provide a review of the psychological, relational and sexual issues experienced by women with vulvar cancer in order to highlight the importance of this issue and improve the quality of care offered to these patients. A review of the literature was performed using PubMed, CINAHL, PsycINFO, and the Cochrane Library. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…When addressing surgical treatment options following vulvar cancer excision, it is important to keep in mind the sexual and functional outcomes of reconstructive surgery in comparison to primary closure [ 22 , 23 ]. This component was not included in this paper, but it will be the focus of our near future research.…”
Section: Discussionmentioning
confidence: 99%
“…When addressing surgical treatment options following vulvar cancer excision, it is important to keep in mind the sexual and functional outcomes of reconstructive surgery in comparison to primary closure [ 22 , 23 ]. This component was not included in this paper, but it will be the focus of our near future research.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 , 17 , 18 , 19 , 20 With the increased understanding of human health and the consequent advancements in healthcare, the role of socio‐psychosocial factors in cancer is receiving increased attention. Several clinical studies have shown that socio‐psychosocial factors are important prognostic factors in a variety of tumor types in both adults and adolescents, 21 , 22 , 23 , 24 and marital status is one of the most important socio‐psychosocial factors. 25 , 26 , 27 Recent studies have focused on marital status and cancer, and the results suggest that married patients have significantly better survival than unmarried patients.…”
Section: Introductionmentioning
confidence: 99%
“… 26 31 Thus, the main complaints of affected women resulting from this treatment is the high risk of psychological distress, low libido, and dissatisfaction in the relationship with their partner. 60 61 And because vulvar cancer is a neoplasm with a rare condition, there is scarcity of studies on the impact of the disease and little is known about the real emotional, social, and psychological impacts on surviving patients. 2 4 8 Studies suggest that, for these cases, the care strategy that can be offered to surviving patients is psychological and therapeutic support, because many of them have significant levels of suffering, with an altered perception of their body image and feelings of isolation and embarrassment resulting from external genital mutilation.…”
Section: Discussionmentioning
confidence: 99%
“… 15 19 In the biopsychosocial aspect, this has a very relevant factor, because many of them feel unprepared and without the correct information of care, which brings a negative psychological, social, and even financial burden, because in many situations it is necessary to give up the job to be able to give the support that the patient needs. 11 13 60 Intimate intercourse is a psychosocial process strongly experienced in the female sexual function and many difficulties faced by surviving women are a result of this. 19 34 In addition, sexual dysfunctions are closely linked to the stages of the cycle of sexual response, that is, the inability of the sexual act to be satisfactory for the couple.…”
Section: Discussionmentioning
confidence: 99%